Kinematic comparison of the seoi-nage technique between top-elite and sub-elite judo athletes - Ishii, T.; Ae, M.; Koshida, S.; Suzuki, Y.; Kobayashi, Y.; Fujii, N. (The Arts and Sciences of Judo, 2021)
This study sought to identify biomechanical factors that determine highly skilled seoi-nage technique by comparing kinematics between top-elite and sub-elite judo athletes. Three-dimensional motion data were captured using a Vicon-MX system with 18 cameras operating at 250 Hz as 3 male top-elite and 16 male sub-elite judo athletes performed seoi-nage. No significant difference was found in motion phase time of the kuzushi/tsukuri phase between the two groups, indicating that motion phase time is not necessarily a factor distinguishing between the seoi-nage performed by top-elite judo athletes and that performed by sub-elite athletes. The peak relative velocity of the whole-body centre of mass along the anterior-posterior direction appeared to be greater in the top-elite athletes (median: 2.62 ± 0.25 m/s) than in the sub-elite athletes (median: 1.62 ± 0.28 m/s) during the kuzushi/tsukuri phase (p = 0.05). The overall angular velocity of the body part lines was similar in both groups; however, the timing at which the peak values appear may distinguish between the top-elite and sub-elite judo athletes. The results imply that the velocity of the thrower relative to the uke in the forward drive and turning motion reflects a high-skill seoi-nage. Coaches should recognise relative forward velocity as a factor that may contribute to a successful seoi-nage when teaching this judo throwing technique.